Impulsivity is associated with food intake, snacking, and eating disorders in a general population. Issue 1 (29th December 2018) - Bénard, Marc; Bellisle, France; Kesse-Guyot, Emmanuelle; Julia, Chantal; Andreeva, Valentina A; Etilé, Fabrice; Reach, Gérard; Dechelotte, Pierre; Tavolacci, Marie-Pierre; Hercberg, Serge; Péneau, Sandrine
ABSTRACT: Background: Impulsivity is a psychological trait linked to health issues such as obesity. However, few studies have explored the relation between impulsivity, dietary intake, and eating disorders (EDs) in a general population. Objective: The aim of this cross-sectional study was to assess whether impulsivity was associated with energy intake, food-group consumption, snacking, and risk of EDs. Design: In 2014, 51, 368 adult participants from the NutriNet-Santé Study completed the 11th version of the Barratt Impulsiveness Scale (BIS-11), which assesses impulsivity. Food-group consumption and diet quality were evaluated by using ≥3 self-reported 24-h dietary records ( n  = 35, 830), whereas snacking behavior was evaluated by an ad hoc question ( n  = 48, 562). Risk of EDs was assessed with the Sick-Control-One-Fat-Food Questionnaire (SCOFF), and categories of ED (restrictive, bulimic, hyperphagic, and other types of EDs) were determined with the Expali algorithm ( n  = 48, 824). Logistic and linear regressions were used to analyze the associations between impulsivity and energy intake, food-group consumption, diet quality, snacking, and risk of EDs, taking into account sociodemographic and lifestyle factors. Results: Positive associations were found between impulsivity and consumption of alcoholic beverages and appetizers, whereas negative associations were found for fruit and vegetables, meat and poultry, processed meat, dairy products, milk-based desserts, and starchy foods. Impulsivity was positively associated with energy intake and negatively associated with diet quality. Impulsivity was also positively associated with snacking (OR: 3.32; 95% CI: 2.99, 3.68) and risk of EDs (OR: 3.02; 95% CI: 2.74, 3.33). The strongest associations were found for bulimic disorders (OR: 4.38; 95% CI: 3.66, 5.23) and hyperphagic disorders (OR: 2.91; 95% CI: 2.56, 3.31). Conclusion: Impulsivity was associated with food intakes, snacking, and risk of EDs and could be taken into account in the promotion of healthy eating behavior. This study was registered at clinicaltrials.gov as NCT03335644.